Design of 3-22kV 70MVA aboveground substations and installation of electrical equipment for Phase 1 of the Jurong Rock Cavern Project - Banan, Celestino L. Jr. (Manila Professional Regulation Commission, 2015)
The 22 kV switchgear assembly is GIS Design and construction with metal clad enclosure and fixed type circuit breaker. Each of the 22kV outgoing circuit breakers is complete with an earthing switch with interlock such that when the circuit breaker is close, the earthing switch shall be un able to close and vice versa. The assembly is extendable from either and for future expansion. The HV circuit breakers is design that guarantees the transient voltages or switching surge voltages caused by current chopping, pre-strike switching, restrike switching or virtual chopping by such a device are being curbed to a safe level without the use of surge suppressor circuit. The equipment interfacing, control, alarm trip and signal status signal wiring shall be properly tagged and terminated in a centralized location of the switchgear to facilitate convenient termination of cab lings. The switchgear is provided by gas monitoring relay and alarm. The JRC substation is directly supplied from the 22 kV Singapore power grid. The 22 kV line has very good power stability. The good power stability helps to operate the products from ships, metering, product and water seepage pumps, access lift, ventilation and ACU in stable mode. We anticipate power failures during operation, which may due to natural disasters. The 22 -kV system is relatively sustainable further underscores why this system will emerge as the main element of power distribution system in the years ahead.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-673G donated by Mr. Jaime V. Mendoza.
Keywords: Electric substations